Fate of Listeria monocytogenes in the Presence of Resident Cheese Microbiota on Common Packaging Materials - Di Ciccio, Pierluigi; Rubiola, Selene; Grassi, Maria Ausilia; Civera, Tiziana; Abbate, Francesco; Chiesa, Francesco (Frontiers in Microbiology, 2020)
Literature data regarding the survival of microorganisms on materials used for food package purposes are scarce. The aim of the current study is to assess the survival of Listeria monocytogenes on different packaging materials for dairy products during extended storage at different temperatures. Three packaging materials (5x5 cm) were contaminated with a cocktail of five strains of Listeria monocytogenes suspended in a cheese homogenate including the cheese’s native microbial population. Contaminated samples were incubated at 37°, 12° and 4°C and periodically analyzed up to 56 days. The evolution of the total viable count and pathogen population was evaluated. At 37°C, the results showed that Listeria monocytogenes was no longer detected on polyethylene-coated nylon (B) by day 4 and on polyethylene-coated parchment (A) and greaseproof paper (C) by day 7. Interestingly, the initial cell population (ranging between 2.5 - 2.7 log CFU/cm2) of Listeria monocytogenes increased to 3 log CFU/cm2 within 4 days of storage at 12°C on A and C. During storage, the number remained fairly constant at 12°C and 4°C on two materials (A – C), and decreased slowly on the third one (B). This study shows that survival of Listeria monocytogenes on packaging materials for dairy products will be higher when stored at 4°C or 12°C compared to 37ºC. The survival of Listeria monocytogenes on the packaging materials raises concerns of cross-contamination during food handling and preparation at catering and retail premises and within the home, highlighting the importance of treating the packaging materials as a potential source of cross-contamination. These initial findings may aid in quantifying risks associated with contamination of food packaging materials.